2017
DOI: 10.5194/hess-21-3061-2017
|View full text |Cite
|
Sign up to set email alerts
|

Water footprint of crop production for different crop structures in the Hebei southern plain, North China

Abstract: Abstract. The North China Plain (NCP) has a serious shortage of freshwater resources, and crop production consumes approximately 75 % of the region's water. To estimate water consumption of different crops and crop structures in the NCP, the Hebei southern plain (HSP) was selected as a study area, as it is a typical region of groundwater overdraft in the NCP. In this study, the water footprint (WF) of crop production, comprised of green, blue and grey water footprints, and its annual variation were analyzed. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…We found that, although 2H1Y OPT increased grain yield (5.97%) and reduced N fertilizer (61.81%) as compared to 2H1Y FP , the 610 mm irrigation consumption is still high. The high water use in the double cropping system also reported by many other researchers [60][61][62]. Therefore, only N saving is unsustainable, because irrigation water is quite important factor in the crop production system.…”
Section: Effect Of Different Cropping Systems On Grain Yield Water Amentioning
confidence: 79%
“…We found that, although 2H1Y OPT increased grain yield (5.97%) and reduced N fertilizer (61.81%) as compared to 2H1Y FP , the 610 mm irrigation consumption is still high. The high water use in the double cropping system also reported by many other researchers [60][61][62]. Therefore, only N saving is unsustainable, because irrigation water is quite important factor in the crop production system.…”
Section: Effect Of Different Cropping Systems On Grain Yield Water Amentioning
confidence: 79%
“…However, the water consumption values of different agricultural products strongly diverge, as shown in a comparison by Hoekstra and Mekonnen for crops and dairy products (Mekonnen and Hoekstra 2012a;Stoessel et al 2012). Specific attention should be devoted to agricultural products requiring high amounts of freshwater that are usually grown in water-scarce regions and/or seasons (Chapagain and Orr 2009;Chu et al 2017).…”
Section: High-priority Activitiesmentioning
confidence: 99%
“…China is the largest consumer of the world's limited water resources, and the proportion of agricultural water in its total water consumption is greater than 70% [2,3]. Groundwater is an essential source for agricultural irrigation, accounting for nearly 10% in China [4,5]. In the vast land of Northwest China, there are numerous large and small oases.…”
Section: Introductionmentioning
confidence: 99%